Quality and communicability for interactive hypermedia systems : concepts and practices for design - Cipolla-Ficarra, Francisco V. (Francisco Vicente), 1963- (Information Science Reference, 2010)
"This book introduces a new professional in the context of the information science, technology, and management called an 'heuristic assessor of qualitative communicability in interactive systems'"--Provided by publisher.